(untitled) (Heritage, 2023)
Within the current processes of globalization and integration of modern economic trends and intensive migration trends, the focus of interest, not only experts but also the public in general, are increasingly coming preservation of national, linguistic and religious identity. In accordance with the scientific significance of the research of ethnicity, linguistic and religious identity, this paper studies language and religion as important components of national identity, their importance in defining nations and national issues, as well as changes caused by numerous political factors.Empirical research has shown that there is a match between nationality and mother tongue (ethnophony), while the occurrence of a greater or lesser deviation (alterophony) is present in the fewer and sparsely dispersed ethnic communities. Regarding religion, the population of Serbia is declared to the greatest extent by the tradition, that is, the religion of parents, which is why there is a high degree of compatibility between nationality and religion. Comparison of census data shows a significantly smaller number of atheists at the beginning of the 21st century, and the reasons for this should be sought in the revitalization of religion and the action of complex political, socio-cultural and socio-historical factors in Serbia.